Pengaruh Pemasaran Relasional dan Citra Merek Terhadap Loyalitas Pelanggan Pada Waralaba Internasional di Tengah Konflik Palestina : (Studi Pada Konsumen Mcdonald’s di Kota Bandar Lampung) - Gusthia Wahyuni; Ridwansyah Ridwansyah; Muhammad Iqbal Fasa (Pusat Riset dan Inovasi Nasional, 2024)
Boycotting products has become a phenomenon that has garnered global attention, especially in the context of the conflict between Israel and Palestine. As one of the largest fast-food brands in the world, McDonald's has been targeted for boycotts by several groups and individuals who oppose the company's policies and practices perceived to be involved in the conflict. This research aims to analyze the influence of relational marketing and brand image on customer loyalty in international franchises amid the Palestinian conflict. The study uses purposive sampling techniques with a Likert scale distributed to 100 McDonald's consumers via Google Forms, tested using IBM SPSS Statistics 26. The results of the study indicate that the variable of relational marketing does not have a positive and significant effect on customer loyalty. However, for the second hypothesis, brand image has a positive and significant effect on customer loyalty. It can be concluded from the test results that the variables of relational marketing and brand image simultaneously have a positive and significant effect on customer loyalty.